2021
DOI: 10.1021/jacs.1c01770
|View full text |Cite
|
Sign up to set email alerts
|

Meta Selective C–H Borylation of Sterically Biased and Unbiased Substrates Directed by Electrostatic Interaction

Abstract: An electrostatically directed meta borylation of sterically biased and unbiased substrates is described. The borylation follows an electrostatic interaction between the partially positive and negative charges between the ligand and substrate. With this strategy, it has been demonstrated that a wide number of challenging substrates, especially 4-substituted substrates, can selectively be borylated at the meta position. Moreover, unsubstituted substrates also displayed excellent meta selectivity. The reaction em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 57 publications
1
35
0
1
Order By: Relevance
“…While indeed bipyridines with electron-withdrawing substituents effectively interacted with sulfonate-substituted anilines resulting in their meta -selective C–H borylation, electron-poor phenanthroline proved to be ideally suited to interact with a broad range of different sulfamates and amides (Scheme 30 ). 89 Even 1,4-disubstituted arenes, such as the 4- t Bu-substituted substrate 115d , which are considered to be challenging for meta -selective borylation due to the steric shielding, 8b were converted into the borylated products, e.g. 116d , in a highly selective manner.…”
Section: Trends In C–h Borylation Reactionsmentioning
confidence: 99%
“…While indeed bipyridines with electron-withdrawing substituents effectively interacted with sulfonate-substituted anilines resulting in their meta -selective C–H borylation, electron-poor phenanthroline proved to be ideally suited to interact with a broad range of different sulfamates and amides (Scheme 30 ). 89 Even 1,4-disubstituted arenes, such as the 4- t Bu-substituted substrate 115d , which are considered to be challenging for meta -selective borylation due to the steric shielding, 8b were converted into the borylated products, e.g. 116d , in a highly selective manner.…”
Section: Trends In C–h Borylation Reactionsmentioning
confidence: 99%
“…Significant approaches have been made to achieve ortho ‐borylation of various substituted arenes [16] . As meta ‐ and para ‐C−H bonds are far away from the directing group but are adjacent to each other, it is more challenging to realize meta ‐ and para ‐selective borylation of aromatics [11, 17] . The Chattopadhyay group developed a tunable ortho ‐ and meta ‐C−H borylation of aromatic aldehydes via in situ generated imines.…”
Section: Introductionmentioning
confidence: 99%
“…Especially the metal-catalyzed C–H borylation, featuring environmental friendliness and atom economy, has been one of the most practical methods to produce highly versatile aryl organoboronate ester intermediates, borylated thiophenes, and borylated heterocycles . Nevertheless, improving both the activity and selectivity of the C–H borylation reaction still presents a challenge associated with the inertness and abundance of C–H bonds in organic molecules. …”
Section: Introductionmentioning
confidence: 99%
“…Introducing suitable pendent groups on the ligand skeleton has been suggested to be an effective strategy to endow transition-metal catalysts with good selectivity in C–H activation reactions by forming intramolecular directing interactions with substrates . As shown in Figure , the metal catalysts with hydrogen-bonding (a–d), ion-pairing (e), electrostatic (f,g), , and Lewis acid–base (h,l) directing interactions have been developed and good selectivity has been achieved. Recently, Chattopadhyay et al reported a series of ligand-enabled ortho , meta , and para C–H activation for aromatic complexes through noncovalent interactions. ,,,, In 2018, Smith and Chattopadhyay reported that the hydrogen-bonding interactions between the PhN­(H)­Beg substrate and O atoms in the directing Beg group led to a high ortho -selectivity (97%) in the Ir-catalyzed C–H borylation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation